The anthropology of the future - Bryant, Rebecca 1970- (New departures in anthropology (Cambridge University Press), 2019)
Study of the future is an important new field in anthropology. Building on a philosophical tradition running from Aristotle through Heidegger to Schatzki, this book presents the concept of 'orientations' as a way to study everyday life. It analyses six main orientations - anticipation, expectation, speculation, potentiality, hope, and destiny - which represent different ways in which the future may affect our present. While orientations entail planning towards and imagining the future, they also often involve the collapse or exhaustion of those efforts: moments where hope may turn to apathy, frustrated planning to disillusion, and imagination to fatigue. By examining these orientations at different points, the authors argue for an anthropology that takes fuller account of the teleologies of action